KARRIKIN INSENSITIVE2 regulates leaf development, root system architecture and arbuscular‐mycorrhizal symbiosis in Brachypodium distachyon. (23rd February 2022) - Meng, Yongjie; Varshney, Kartikye; Incze, Norbert; Badics, Eszter; Kamran, Muhammad; Davies, Sabrina F.; Oppermann, Larissa M. F.; Magne, Kévin; Dalmais, Marion; Bendahmane, Abdel; Sibout, Richard; Vogel, John; et al.
SUMMARY: KARRIKIN INSENSITIVE2 (KAI2) is an α/β‐hydrolase required for plant responses to karrikins, which are abiotic butenolides that can influence seed germination and seedling growth. Although represented by four angiosperm species, loss‐of‐function kai2 mutants are phenotypically inconsistent and incompletely characterised, resulting in uncertainties about the core functions of KAI2 in plant development. Here we characterised the developmental functions of KAI2 in the grass Brachypodium distachyon using molecular, physiological and biochemical approaches. Bdkai2 mutants exhibit increased internode elongation and reduced leaf chlorophyll levels, but only a modest increase in water loss from detached leaves. Bdkai2 shows increased numbers of lateral roots and reduced root hair growth, and fails to support normal root colonisation by arbuscular‐mycorrhizal (AM) fungi. The karrikins KAR1 and KAR2, and the strigolactone (SL) analogue rac ‐GR24, each elicit overlapping but distinct changes to the shoot transcriptome via BdKAI2. Finally, we show that BdKAI2 exhibits a clear ligand preference for desmethyl butenolides and weak responses to methyl‐substituted SL analogues such as GR24. Our findings suggest that KAI2 has multiple roles in shoot development, root system development and transcriptional regulation in grasses. Although KAI2‐dependent AM symbiosis is likely conserved within monocots, the magnitude of the effect of KAI2 on water relations may vary across angiosperms. Significance Statement: KAI2 is an α/β‐hydrolase receptor for abiotic karrikins and yet elusive plant hormones. The roles of KAI2 have been extensively studied in the dicotyledon Arabidopsis. Here we provide a comprehensive characterisation of the roles of KAI2 in the monocotyledon Brachypodium distachyon .